Pengaruh Koleksi Perpustakaan Terhadap Misssnat Baca Mahasiswa Sekolah Tinggi Teologi Baptis Medan - Gita Rimayati Situmorang; Rogate A.T Gultom; Robinhot Sihombing (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to determine the influence of library collections on the reading interest of Medan Baptist Theological College students. This research uses a quantitative approach with inferential statistics. With a total population of 88 Medan Baptist Theological College students in 2023. Data was collected using a 30-item questionnaire compiled by the author based on variable indicators according to theory. The results of data analysis show that there is a positive and significant influence in the Library Collection on the Reading Interest of Medan Baptist Theological College Students: 1) Test the analysis requirements: a) test the positive influence, the value rxy = 0.462 > rtable (=0.05, n=31) = 0.355, thus it is known that there is a positive influence between variable Thus, there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 21.31%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable, namely 7.854>4.00. Thus Ha is accepted and H0 is rejected.